Dampak Pergeseran Wilayah Akibat Naiknya Permukaan Laut dan Dampakya Bagi Navigasi - Enny Narwati; Dina Sunyowati; R. Yahdi Ramadani (Media Iuris, 2022)
AbstractRising sea levels are caused by climate change and global warming which is characterized by an increase in air temperature, especially the earth’s atmosphere. Rising sea levels can cause accretion or erosion of a country which causes a shift in the boundaries of the coastal state. This natural phenomenon becomes a problem in determining the baseline of the coastal state territory because international law of the sea has not specifically regulated the shift in the boundaries of the coastal state due to climate change and global warming. This study examines the legal consequences of shifting state sea boundaries due to climate change according to international law and the rights of third countries to shifting state sea boundaries due to climate change. A third State may advise the coastal State to update baselines and maps of areas lost due to rising sea levels to the Secretary-General of the United Nations. This action can provide benefits for all parties, especially disadvantaged countries or ship owners to experience the Freedom of Navigation in the renewed territory. AbstrakNaiknya permukaan laut disebabkan oleh perubahan iklim dan pemanasan global yang ditandai dengan peningkatan suhu udara atmosfer bumi. Naiknya permukaan laut dapat mengakibatkan akresi ataupun erosi suatu negara yang menyebabkan terjadinya pergeseran batas wilayah negara pantai. Fenomena alam tersebut menjadi permasalahan terhadap penetapan garis pangkal wilayah negara pantai dikarenakan hukum laut internasional belum mengatur secara khusus mengenai pergeseran batas wilayah negara pantai akibat perubahan iklim dan pemanasan global. Penelitian ini mengkaji akibat hukum pergeseran batas wilayah laut negara akibat perubahan iklim menurut hukum internasional dan hak negara ketiga terhadap pergeseran batas wilayah laut negara akibat perubahan iklim. Negara ketiga dapat menyarankan kepada negara pantai untuk memperbarui garis pangkal dan peta wilayah yang hilang akibat naiknya permukaan laut kepada Sekretaris Jendral Perserikatan Bangsa-Bangsa. Tindakan tersebut dapat memberikan keuntungan bagi semua pihak terutama negara-negara yang kurang beruntung ataupun negara pemilik kapal untuk merasakan Freedom of Navigation diwilayah yang telah diperbarui.